Monopoly Distortions in Durability and Multi-Dimensional Quality - Roland Strausz (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2009)
I show that Swan's (1970) independence result requires a multiplicative interaction between durability and all other quality attributes. Because there is no compelling argument for a multiplicativity in quality, monopolists tend to distort durability, even with constant marginal costs. Distortions in durability and other quality aspects are aligned exactly when the marginal cost of quality do not increase too much with durability.
urn:nbn:de:bvb:19-epub-13281-0
Keywords: 330; Durability; quality; monopoly